Las medidas ejecutivas - Vilela Carbajal, Karla Patricia Maribel (Revista de Derecho, 2019)
The article has as its objective the study of executive measures, due to the fact that in practice they are mistaken with injunctions. For this, as a first step, injunctions are briefly studied and their main features are pointed out. Then the concept of executive measures is analyzed and its main differences with injunctions are then determined. Finally, the article is centered in the study of the expiration of executive measures, that is, it is about finding whether executive measures ruled under the PCC of 1993 have an expiration date for which all national legislation is developed (with all its modifications) and the posture of the doctrine and of the tribunals belonging to Public Registries and the Judicial Power.